The effect innovation cloning to small business success: Entrepreneurial perspective - Harmon Chaniago (Journal of Innovation and Entrepreneurship, 2022)
It is challenging to run a business during the COVID-19 pandemic, because the owners and the small business leaders must be responsible for success. Leaders need to innovate and look for sources of innovation, including practical inventions, such as innovation cloning. In this study, innovation cloning consisting of creativity cloning and implementation cloning is analyzed for its relationship to business success, in the form of owner's interest and financial performance perspectives. This study aims to reveal the role of innovation cloning, creativity cloning, and implementation cloning in achieving business success based on the owner's interest and financial performance. The study uses an explanatory survey. The number of samples is 155 entrepreneurs/small business leaders in Bandung City, Indonesia. Snowball sampling is carried out to obtain the data. Data processing uses descriptive statistics and multiple regression with the help of SPSS and Amos 23 software. This study found that creativity cloning and implementation cloning affected the owner's interest, and implementation cloning affected financial performance. In contrast, creativity cloning does not affect financial performance. Creativity cloning and implementation cloning are correlated with each other. Creativity cloning and implementation cloning are proved to be one unit of cloning innovation. The leader's expertise in choosing the object to be cloned and adapting it to consumer needs will facilitate company goals. Utilizing innovation, cloning, and modifying it is a practical way for small businesses to succeed. This research needs to be continued to see if there is a continuous pattern in these findings so those findings can be generalized.
Keywords: 650; Creativity; Customer-oriented; Financial performance; Implementation; Innovation cloning; Owner's interest